1999
DOI: 10.1128/jb.181.4.1229-1237.1999
|View full text |Cite
|
Sign up to set email alerts
|

Impact of either Elevated or Decreased Levels of Cytochrome bd Expression on Shigella flexneri Virulence

Abstract: Shigella spp. are the major cause of bacillary dysentery worldwide. The pathogenic process involves bacterial invasion and lysis of the phagocytic vacuole, followed by replication and movement within the cell cytoplasm and, ultimately, spread directly into adjacent cells. This study demonstrates that S. flexneri cytochrome bd expression is necessary for normal intracellular survival and virulence. Cytochrome bdis one of two terminal oxidases in the bacterial respiratory chain that reduce molecular oxygen to wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 41 publications
(54 reference statements)
2
48
0
Order By: Relevance
“…Mutations in genes of the ETC are often associated with SCVs, however the diversity of mutational targets that can give rise to such SCVs is poorly understood. Our results (Table S2) & Goldberg, 1999). We confirmed this result in our SCV clone, by demonstrating that (i) ubiH expression was strongly reduced in the pepP mutant (clone 41; Fig.…”
Section: Novel Genetic Targets Associated With the Etc Mediate Thsupporting
confidence: 85%
“…Mutations in genes of the ETC are often associated with SCVs, however the diversity of mutational targets that can give rise to such SCVs is poorly understood. Our results (Table S2) & Goldberg, 1999). We confirmed this result in our SCV clone, by demonstrating that (i) ubiH expression was strongly reduced in the pepP mutant (clone 41; Fig.…”
Section: Novel Genetic Targets Associated With the Etc Mediate Thsupporting
confidence: 85%
“…A MxiG derivative in which an internal RGD motif is replaced by RAD can secrete the Ipas and is invasive, but is unable to mediate proper bacterial contact with the protrusion membrane and, as such, forms abnormally small plaques. Other mutations that affect cell-to-cell spread include those that speci®cally inhibit intracellular septation (MacSõ Âomo  in et al, 1996), alter cytochrome bd expression (Way et al, 1999), destabilize the cytoplasmic membrane or peptidoglycan layer (Hong et al, 1998) or prevent periplasmic oxidative protein folding (Yu, 1998). No experiments have yet been reported that speci®cally implicate Ipa secretion in any post-invasion functions within epithelial cell or epithelial cell-like lines.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, E. coli cytochrome bd-I was proved to provide the oxidizing power required both by the DsbA-DsbB system to catalyze disulfide bond formation during protein folding [91] and by protoporphyrinogen IX oxidase (HemG), an enzyme involved in heme biosynthesis [92]. It is worth mentioning that the expression of cytochrome bd oxidases was documented in a number of bacterial pathogens, such as Salmonella [7,10], Mycobacterium tuberculosis [12], Shigella flexneri [8], Streptococcus [13], Listeria monocytogenes [15], Brucella [9,14], members of the strict anaerobe Bacteroides class [11], Klebsiella pneumoniae [6], and for some of these pathogens a correlation between enzyme levels and virulence was observed. Particularly interesting is the case of Mycobacterium tuberculosis in which a transient up-regulation of cytochrome bd was observed in vivo in the transition from acute to chronic infection of mouse lungs, along with a reduced virulence of a mutant strain defective in the cytochrome bd-associated transporter CydC [12].…”
Section: Impact On Microbial Physiologymentioning
confidence: 99%
“…Beyond its role in energy metabolism, a large body of evidence suggests that the enzyme plays alternative functions relevant to physiology and, more specifically, to bacterial adaptation to a wide variety of stress conditions [3,5]. This respiratory oxidase has been identified in a number of pathogens [6][7][8][9][10][11][12][13][14][15] and, in some cases, its expression level was intriguingly found to positively correlate with virulence. Evidence suggests that cytochrome bd is implicated in adaptation to the hostile conditions created by host immunity during the infection process, though the molecular mechanism(s) through which the enzyme operates to enhance bacterial resistance have been only partly clarified.…”
Section: Introductionmentioning
confidence: 99%